Information Communication and Technology Tools for Education and Learning by Animation and Multimedia Learning System (International Journal of Emerging Trends in Science and Technology, 2017)
The purpose of this paper aims to bring together the findings and key points from a review of significantpart of the available literature associated with ICTs for effective learning and teaching and ICTs inEducation. This review set out to understand this thesis works in a simple way, the following basicconcepts such as Education, Memory and Learning, Attention, Sensation and Perception, Learning andTeaching, multimedia and Learning, Multimedia Learning System are very useful. This section explainsthe basic aspects related to this research work.